Optimalisasi Deformasi Canai Dingin untuk Meningkatkan Sifat Mekanik Paduan Al-Mg-Si - Venty Lestari (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The demand for lightweight materials with high mechanical strength has driven the development of aluminum alloys, particularly Al-Mg-Si, through deformation processes such as cold rolling. This study aims to analyze the effect of varying degrees of cold rolling deformation on the grain aspect ratio and macrohardness of homogenized Al-Mg-Si alloys. Deformation was applied at three thickness reduction levels—5%, 10%, and 20%—followed by microstructural characterization using optical microscopy and macrohardness testing in accordance with ASTM E-18 standards. The results show that increasing deformation levels lead to elongated grain morphology, with the grain aspect ratio rising from 1.16 to 2.07 and macrohardness increasing from 46.64 HRE to 62 HRE. The emergence of slip lines and grain flattening indicates the occurrence of intense plastic deformation, while work hardening results from dislocation accumulation that impedes further slip motion. These findings confirm a strong correlation between microstructural evolution and mechanical property enhancement in cold-deformed Al-Mg-Si alloys. This research contributes to the optimization of cold rolling parameters to produce engineering materials with a desirable balance of strength, formability, and fatigue resistance for applications in the mining and heavy manufacturing industries.